Phenotypic method for differentiation of carbapenemases in Enterobacteriaceae: Study from north India - Priya Datta; Varsha Gupta; Shivani Garg; Jagdish Chander (Wolters Kluwer Medknow Publications, 2012)
Aims: Carbapenems are usually the choice of antimicrobials in infections caused by Enterobacteriaceae bacteria-producing ESBL (extended spectrum β-lactamases) and Amp C. Resistance to carbapenems is mostly due to production of enzymes - Carbapenemases, which are divided into Ambler Classes A, B and D. Phenotypic detection and differentiation of types of Carbapenemases in carbapenem-resistant Enterobacteriaceae (CRE) is important for proper infection control and appropriate patient management. Materials and Methods: The present study done in a tertiary care hospital from North India differentiates Class A (KPC type) and B (MBL type) carbapenemases among Enterobacteriaceae isolates by simple phenotypic method that uses both the inhibitors EDTA and phenylboronic acid. Results: Total of 330 strains of Enterobacteriaceae were included in the study. Out of these 330 strains, 26 strains were resistant to carbapenems. The prevalence of CRE in our Institute is 7.87% (26/330). Conclusions: The prevalence of Enterobacteriaceae strains producing MBL type carbapenemase in our health care setup is 5.75% (19/330). None of the strains among the carbapenem-resistant bacterial isolates showed production of KPC enzyme. The need of the hour is simple, rapid and cost effective tests which will be able to identify and distinguish resistant pathogens for improved patient outcome, facilitating efficient infection control and reducing the escalation of resistance.